Propagation of quality planting materials: a training manual - Mercado, A.; Linayao, J.C.; Duque-Piñon, C. (World Agroforestry Centre, 2020)
This manual is written particularly for 1) extensionists working in agroforestry and natural resources management projects; and 2) farmers, especially those who want to share their agroforestry knowledge with their fellow farmers. The manual can be used as reference material for training sessions and other learning activities.